Experimental investigation on biological hydrogen production using different biomass - Agrawal, Pushpa; R., Hema; S., Mahesh Kumar (2006)
Hydrogen is a clean and efficient fuel, considered as a potential and more sustainable energy substitute for fossil fuels. Biological hydrogen production stands out as an eco friendly process carried out under mild operating conditions with renewable resources. In the current work laboratory scale production of hydrogen using phototrophic purple non-sulphur bacteria Rhodobacter sphaeroides, anaerobic dark fermentative bacteria’s Clostridium pasteurinum, Bacillus licheniformis and Enterobacter clocae with different substrates was investigated. The study mainly emphasized on assessing the potential of biological conversion of different substrates to hydrogen by studying various experimental parameters like temperature, pH and cell density. It was found that the Rhodobacter sphaeroides took relatively longer duration (48 hrs) for hydrogen production. The optimum temperature and pH for maximum production of hydrogen in case of Rhodobacter sphaeroides was found to be 32° C and 7.5 respectively, 32°C and 7 for Clostridium pasteurinum respectively, 30°C and 6.8 respectively for Bacillus licheniformis and Enterobacter clocae. Results of the batch tests depicted that Rhodobacter sphaeroides produced maximum amount of hydrogen (35%) as compared to 21% by Clostridium pasteurinum, 16% by Bacillus licheniformis and 8% by Enterobacter clocae. However the quantity of hydrogen production in case of Rhodobacter sphaeroides was relatively lower compared to Clostridium pasteurinum.